Performance of small automatic irrigation canal structures under laboratory and field conditions - Pradhan, Niranjan; Loof, Rainer; Paudyal, Guna N.; Preecha Kamronrithisorn; The Government of Japan (Bangkok : Asian Institute of Technology, 1989)
The present research emphasizes on the calibration and evaluation of an automatic downstream control AVIO Gate and constant flow distributors. In the laboratory, also the leakage through the emergency gate and the AVIO Gate were studied. The modules were tested both for downstream submerged flow and free flow conditions. From submerged flow data, an attempt was made to develop nomographs which can be used as a tool to determine the flow through the modules for any submergence and upstream and downstream head difference by interpolation. Under downstream submergence, the commencement of orifice flow for Single Baffle Module could not be ascertained due to more effect of submergence. But for the Double Baffle Module except the first falling stage the second falling stage could be ascertained, which shows that the module is more suitable for submerged condition. In case of free flow for both the modules, this falling stage nature is clearly seen within the specified head range above the sill. The coefficients of discharge for weir flow and orifice flow have been determined. From the performance study of the gate separately and associated with modules it is seen that the constant downstream level control gate is really an effective means of making more rational use of available water supplies and of running canal systems on a more economical basis. It also provides an attractive and original answer to the problem of equipping water offtakes and other free surface control works required to maintain a definite downstream water level. The actual flow through the distributors in downstream free flow condition varies from the design flow rates at 5% to 15% and in downstream submerged condition the flow rate variation remains within the range of 20% to 30%.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1989
Keywords: Irrigation -- Management; Irrigation -- Automation